Demographic Characteristics of Patients Attending at National Fistula Centre with Vesicovaginal Fistula (Ibrahim Cardiac Medical Journal, 2018)
Background & objective: Obstetric fistula is one of the most dreadful complications encountered in obstetrics and gynaecology and constitute a major surgical challenge for the Gynaecologists. With advanced obstetric care, this fistula is rare in industrialized world but it is still a major health problem in developing countries like Bangladesh. Victims of fistula become physically cripple, socially outcast, psychologically traumatized. Surgical repair can mend this injury. This study describes the demographic characteristics of the patients of obstetric fistula attended at National Fistula Centre, Dhaka Medical College Hospital, Dhaka between January to December 2016.Materials & Methods: This descriptive study was carried out in the National Fistula Centre of the Department of Obstetrics & Gynaecology, Dhaka Medical College Hospital, Dhaka from January 2016 to December 2016. The total number of obstetric fistula patients treated over the 1-year period (n = 50) were consecutively included in the study. Diagnosis was based on the patients' history and examination findings of attending physicians confirmed by the concerned specialist. Other types of fistula other than obstetric were excluded. The fistula was classified into vesicovaginal and rectovaginal fistula. The records were confirmed with the records that were kept by the only surgeons who operated on these patients during the requested period.Results: Forty percent of the patients were 30 – 40 years old with mean age of the patients being 36.6(range: 13-70) years. Over half (54%) of the patients was illiterate, 34% primary level and 10% secondary level educated. All but a single patient was married. Over three-quarters (78%) of the patients were married and were living with their husbands. Majority (98%) was Muslim. The mean age of the patients at marriage was 14 years (range: 6 – 22 years and the mean age at first child birth was 16(range: 12 – 26) years and the mean age at occurrence of fistula was 21.2 (range: 13 – 33) years. One-fifth (20%) of the patients was divorced or separated. Nearly 40% of the patients’ husbands remarried within 6 – 12 months after separation with their previous wives or have had a second marriage. Over 60% of the patients were in a stage of amenorrhoea and the rest were menstruating. Eight (16%) patients reported they have had used contraceptive sometimes in the past. Five out of 8 used contraceptives before the development of fistula and 5 started them using after the development fistula. Majority (86%) of the patients blamed their fate for development of fistula.Conclusion: Obstetric fistula is a preventable and treatable condition, so no woman should suffer from this misery. Direct causes of fistula include premature child bearing, obstructed labour and limited access to emergency obstetric care. Some of the indirect causes, such as poverty, women’s status in the society, and lack of education, prevent women from accessing services that could prevent the onset of such conditionsIbrahim Card Med J 2016; 6 (1&2): 45-50